A Numerically Efficient Method for Predicting the Scattering Characteristics of Complex Moving Targets - Ahmed, Dihia Sidi; Russo, Paola; Cerri, Graziano; Lefevre, Laetitia Thirion; Guinvarc'h, Regis; Manfredi, Giovanni (IEEE transactions on antennas and propagation, 2023)
This paper presents a new computational approach that allows rapid analysis of the Electro-Magnetic Scattering characteristics (EMS) of static or moving complex radar targets. The scattering features of the object are represented through a generalized scattering matrix H, whose elements can be measured or computed using conventional numerical techniques, e.g., CST software in the proposed case, and considering prescribed sampled directions. A cardinal series then is adopted to reconstruct the complete scattering pattern by suitably extending the approach to calculate the target's scattering matrix for any incidence wave and any observation point. The number of finite samples, that is, the dimension of the scattering matrix depends only on the maximum dimension of the target. A PEC sphere and a PEC three-dimensional (3D) complex object have been analyzed in detail. Precise, fast, and stable sampling algorithms have been applied to these targets in the static case and in motion. In particular, the field scattered by the moving objects is then used to carry out the Micro-Doppler analysis of the object radar signature.